Effects of hypochlorous acid mouthwash on salivary bacteria including Staphylococcus aureus in patients with periodontal disease: a randomized controlled trial - Ying-Chu Lin; Cheng-Feng Tsai; Hsiao-Ling Huang (BMC, 2023)
Abstract Background The effects of a low concentration of hypochlorous acid (HOCl) mouthwash on salivary bacteria remained unclear. We aimed to evaluate the antibacterial effects of 100 ppm HOCl mouthwash on salivary bacteria, including Staphylococcus aureus (S. aureus), in patients with periodontal disease (PD). Methods Patients with PD were randomized into mouthwash-only (MW, n = 26) and mouthwash with periodontal flosser (MWPF, n = 27) groups. Patients without PD were selected for the control group (n = 30). S. aureus culture and saliva samples (before and after the intervention) were collected for bacterial DNA extraction. A real-time polymerase chain reaction assay and serial dilutions of S. aureus culture and saliva samples were used to measure the salivary bacteria total count (SBTC) and confirm the antibacterial effects of the mouthwash using S. aureus. Results No significant difference in demographic data was observed among the three groups. Before the intervention, the baseline SBTC of the MW and MWPF groups was significantly higher than that of the control group. After the mouthwash rinses, the SBTC data significantly changed in the MW and MWPF groups only (by 62.4% and 77.4%, respectively). After the base-2 log-transformation of the SBTC data, a similar trend was observed. Linear regression revealed that baseline SBTC and the MWPF intervention significantly affected SBTC reduction percentage by volume. After incubation with 10% (v/v) of mouthwash, the survival rates of 106 and 107 colony-forming units/mL of S. aureus were 0.51% ± 0.06% and 1.42% ± 0.37%, respectively. Conclusions These study results indicated that 100 ppm HOCl mouthwash treatment could effectively reduce SBTC in patients with PD and the abundance of S. aureus. It provides that the HOCl mouthwash can be an option for individuals to help control SBTC, especially in patients with PD. Trial registration The study protocol was approved by the Institutional Review Board of Kaohsiung Medical University Hospital (KMUHIRB-F(I)-20200042) on 20/03/2020 and retrospectively registered at ClinicalTrial.gov (NCT05372835) on 13/05/2022.